By Nature Equal : the Anatomy of a Western Insight. - Coons, John E. (Princeton University Press, 2001)
What do we mean when we refer to people as being equal by nature? In the first book devoted to human equality as a fact rather than as a social goal or a legal claim, John Coons and Patrick Brennan argue that even if people possess unequal talents or are born into unequal circumstances, all may still be equal if it is true that human nature provides them the same access to moral self-perfection. Plausibly, in the authors' view, such access stems from the power of individuals to achieve goodness simply by doing the best they can to discover and perform correct actions. If people enjoy the same.